The use of the long peroneal muscle tendon as an autograft during the primary plastics of the anterior cruciate ligament: a systematic review - Aleksey P. Prizov; Anatoly M. Vostrikov; Dmitry V. Skvortsov; Fedor L. Lazko; Maxim F. Lazko; Evgeniy A. Belyak; Alexandra V. Krytaeva (Клиническая практика)
The anterior cruciate ligament injuries take the leading place among all the injuries of the knee joint. The rupture of the anterior cruciate ligament most frequently occurs during sports-related and high-energy traumas. The aim of the present systematic review is to compare the results obtained after the anterior cruciate ligament plastics with using the long peroneal muscle tendon and the autograft made from the common tendon of the semitendinous and gracilis muscles. The analysis includes the original articles from the PubMed, Google Scholar, eLibrary, Scopus and Web of Science search systems. The key words for the search included (“peroneus longus tendon” or “fibularis longus tendon”) and (“anterior cruciate ligament reconstruction” or “ACL reconstruction”). In the Russian data bases, the same terms were used. From the articles found, the following parameters were extracted: the evaluation of the functional results using the Tegner–Lysholm scale and the questionnaire for subjective assessment of the status among the patients with various knee joint injuries — IKDC (International Knee Documentation Committee); the evaluation of the mean diameter of the autotransplant; the instability of the knee joint; as well as the possible complications; the evaluation of the functions in the ankle joint and the foot using the AOFAS (American Orthopaedic Foot and Ankle Society) and FADI (Foot and Ankle Disability Index) scales. These parameters were used for evaluating the clinical research works on using the autograft made from the long peroneal muscle tendon for the reconstruction of the anterior cruciate ligament. The authors have analyzed the treatment results in 2322 patients which underwent anterior cruciate ligament plastics using the long peroneal muscle tendon (n=1660) and the semitendinous muscle tendon (n=662) autotransplants. The parameters of the postoperative status according to the AOFAS and FADI scales for the long peroneal muscle tendon were 96.47±2.71 and 97.72±2.58, respectively, which does not differ from the uninjured side (p 0.05). The best IKDC scale scores were 94.13±4.66 for the long peroneal muscle tendon and 95.12±0.73 for the semitendinous muscle tendon, while the scores of the Tegner–Lysholm scale were 99.15±2.89 and 99.85±0.37, respectively. Thus, the autograft made using the long peroneal muscle tendon is a proper alternative for the reconstruction of the anterior cruciate ligament, for it is located outside the area of the knee joint.